PEMBENTUKAN MODERASI BERAGAMA MELALUI PENGUATAN SIKAP TOLERANSI ANTAR UMAT BERAGAMA DI PONDOK PESANTREN ASSALAM MANADO - Arief, Muyassir; Humaidi, M. Nurul (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Abstract The formation of religious moderation through strengthening attitudes of tolerance between religious communities is an important step in creating social harmony in a very heterogeneous society.Religious moderation, which prioritizes a wise attitude and a middle path in religion, is one of the main pillars in maintaining peace and unity.In the context of Indonesia which consists of various tribes, religions, and cultures, an attitude of tolerance between religious communities has a crucial role in reducing the potential for conflict and radicalization.Therefore, this study intends to map the values ​​of tolerance that are implemented in living together in diversity through dialogue, exemplary behavior, regulations or local policies that are very inclusive.Understanding the importance of an attitude of religious moderation can lead someone to an attitude of mutual tolerance and respect.Increasing understanding of the importance of religious moderation can distance one from attitudes of extremism.The results of this study indicate that strengthening religious moderation can be realized through an exemplary and togetherness approach, mutual tolerance in the framework of living together in diversity. Keywords: Religious Moderation, Tolerance and Interfaith